Thickness Dependence of Window Layer on CH3NH3PbI3-XClX Perovskite Solar Cell - Wycliffe Isoe (International Journal of Photoenergy, 2020)
CH3NH3PbI3-xClx has been studied experimentally and has shown promising results for photovoltaic application. To enhance its performance, this study investigated the effect of varying thickness of FTO, TiO2, and CH3NH3PbI3-xClx for a perovskite solar cell with the structure glass/FTO/TiO2/CH3NH3PbI3-xClx/Spiro-OMeTAD/Ag studied using SCAPS-1D simulator software. The output parameters obtained from the literature for the device were 26.11 mA/cm2, 1.25 V, 69.89%, and 22.72% for Jsc, Voc, FF, and η, respectively. The optimized solar cell had a thickness of 100 nm, 50 nm, and 300 nm for FTO, TiO2, and CH3NH3PbI3-xClx layers, respectively, and the device output were 25.79 mA/cm2, 1.45 V, 78.87%, and 29.56% for Jsc, Voc, FF, and η, respectively, showing a remarkable increase in FF by 8.98% and 6.84% for solar cell efficiency. These results show the potential of fabricating an improved CH3NH3PbI3-xClx perovskite solar cell.